An effectiveness analysis of a developed differentiated program for dancer's motor quality development at the stage of specialized basic training - Tetiana Trakaliuk (Kharkiv State Academy of Physical Culture, 2017)
Purpose: practical substantiation of the effectiveness of using the developed differentiated program for the development of motor qualities of skilled dancers in sports dances at the stage of specialized basic training. Material & Methods: in the study involved 30 athletes, dancers aged 14-18 years who were engaged in a differentiated program for the development of motor qualities (experimental group) and the generally accepted program of a sports and dance club (control group). Methods: analysis and generalization of information of special literature, method of pedagogical observation, method of pedagogical experiment, method of pedagogical testing, method of mathematical statistics. Result: analysis of the state of special physical preparation of dancers before and after using the developed differentiated program for the development of motor qualities is presented and obtained results of the values of the indices of their leading motor qualities. Conclusion: the efficiency of application of the developed differentiated program for the development of motor qualities of qualified dancers has been proved at the stage of specialized basic training.